A Review of Supercritical Technologies for Lipid-Based Biofuels Production: The Glycerol-free Processes - Winatta Sakdasri; Cholada Komintarachat; Ruengwit Sawangkeaw; Somkiat Ngamprasertsith (My University, 2021)
Supercritical transesterification of lipid-based biomasses, a recent technique to produce biofuel without a catalyst, is discussed.This review focused on a glycerol-free process.The supercritical reactants include dimethyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate (ETA), and methyl tert-butyl ether.The by-products from the glycerolfree process can improve both the quantity and quality of the resultant biofuel.This review suggests that supercritical transesterification of lipid-based biomasses using ETA as a coreactant can provide the most valuable advantages, as involves inexpensive and renewable resources, which are important for biofuel production and sustainability.
Keywords: Microbial Metabolic Engineering and Bioproduction